Positive surgical margins after partial nephrectomy - Pahernik, Sascha; Hohenfellner, Markus (Nature reviews. Urology, 2010)
Small renal tumors are generally managed by partial nephrectomy; however, positive surgical margins are occasionally found on final pathologic examination. Growing evidence suggests that the presence of positive margins does not adversely affect outcomes; these patients can potentially be managed expectantly with close follow-up without compromising oncological efficacy.
Gesehen am 05.07.2023